Prognostic value of the lactate dehydrogenase-to-albumin ratio for predicting mortality in critically ill pediatric patients: a retrospective cohort study - Liu, Ming; Gou, Yunpeng; Yang, Ping (Frontiers in Pediatrics, 2025)
ObjectiveDespite significant advances in pediatric intensive care, the early identification of high-risk critically ill children remains a persistent challenge. This study aimed to evaluate the association between the lactate dehydrogenase-to-albumin ratio (LAR) and mortality outcomes in critically ill pediatric patients.MethodsThis retrospective cohort study analyzed data from the Pediatric Intensive Care (PIC) database (2010–2018) at the Children's Hospital of Zhejiang University School of Medicine. We included 8,782 critically ill patients aged ≥28 days with complete lactate dehydrogenase (LDH) and albumin (ALB) measurements. The LAR was calculated by dividing the serum LDH concentration by the ALB concentration. The primary outcome was 30-day in-hospital mortality, while the secondary outcome was in-hospital mortality. Multivariate Cox proportional hazards regression models were constructed with adjustments for demographic characteristics, clinical parameters, and laboratory variables.ResultsAfter full adjustment for covariates, LAR remained significantly associated with mortality risk. Each 10 U/g increase in LAR was associated with a 3% higher risk of 30-day in-hospital mortality (HR = 1.03, 95% CI: 1.01–1.04, P = 0.005) and a 4% higher risk of in-hospital mortality (HR = 1.04, 95% CI: 1.03–1.06, P < 0.001). Compared to the lowest tertile, the highest tertile had a significantly higher mortality risk (30-day in-hospital mortality: HR = 3.72, 95% CI: 2.50–5.54; in-hospital mortality: HR = 2.68, 95% CI: 1.86–3.87; both P < 0.001). Receiver operating characteristic (ROC) analysis revealed that LAR's discriminative performance (AUC = 0.771 for 30-day in-hospital mortality; AUC = 0.763 for in-hospital mortality) outperformed that of either LDH or ALB alone.ConclusionElevated LAR independently predicts an increased mortality risk in critically ill pediatric patients. As an easily calculated ratio derived from routine laboratory parameters, LAR represents a valuable prognostic tool for risk stratification in the pediatric intensive care setting.